Analysis of Size Effect Anomaly in the Indonesian Stock Exchange: A Study of L-45 Companies for the Period of 2015-2017 - Annisa Shabri; Ambar Pujiharjanto; Sri Budiwati (Journal of Business Innovation and Research, 2023)
The purpose of this study is to analyze the difference in average stock returns between large-sized companies (SBB) and small-sized companies (SBK) in the Indonesian Stock Exchange, focusing on the LQ-45 companies during the period of 2015-2017. The company size is proxied using the market capitalization approach. The analytical tools employed in this research include descriptive analysis, normality test, and paired sample t-test. The research conducted during the period of 2015-2017 reveals that significant differences exist between the returns of large-sized companies (SBB) and small-sized companies (SBK) in the first semester of 2015, first semester of 2016, first semester of 2017, and second semester of 2017. However, no differences in returns between large-sized companies (SBB) and small-sized companies (SBK) are observed in the second semester of 2015 and second semester of 2016..Keywords : Anomaly, Market Anomalies, Size Effect, Stock Return